Differential response to drought, disturbance and increasing temperature of endemic and non-endemic species of a mountain-Mediterranean grassland - Mingo A.; Cristaudo A.; Vitale L.; Magliulo V. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
Autochthonous and widely distributed plant species coexist in most natural pastured grasslands. The aim of this work was to differentiate autochthonous and widely distributed species of a mountain-Mediterranean grassland regarding their ability to face drought and disturbance. A group of species from a natural pasture in the Nebrodi mounts (Sicily) were analysed for their response to light, temperature, water availability and cutting. The species were pot-cultivated and subjected to different experimental treatments. Growth, allocation and plant architecture were determined during the experiments; photosynthetic activity, transpiration and water use efficiency at different temperatures and PPFD were determined by gas-exchange analysis. Local taxa were characterized by different strategies to face water stress, whereas non-endemic pabular species showed higher growth rates and better ability to withstand cutting. The species studied showed different responses to increasing temperatures, pointing out the relevant effects that climatic changes may induce on grassland species composition.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)